Political Economy and Critical Engagement in South Africa: Essays in Honour of Vishnu Padayachee - Bryer, Megan (New Agenda: SA Journal of Social and Economic Policy, 2025)
Vishnu Padayachee was a brilliant intellectual, but more than that, he was an engaged scholar, an activist, a cricket enthusiast and a collector of rare books. The essays in Political Economy and Critical Engagement in South Africa pay tribute to his wide-ranging interests and contributions, offering both personal reflections and rigorous academic engagement with the ideas he championed. Many contributors – colleagues, collaborators and former students of his – wrestle with a question that preoccupied Padayachee: the role of the intellectual in shaping societal change, how scholars can move beyond academic inquiry to influence economic policy and progressive movements